Hubungan Sikap Duduk Dengan Beban Kerja Karyawan PT Trans Marga Jawa Tengah - Marcelino Luki Gunawan Sugiarto; Reni Wijayanti; Farhana Syahrotun Nisa Suratna (Sekolah Vokasi, Universitas Sebelas Maret, 2024)
The problems experienced by Trans Marga Central Java employees are mostly in sitting positions while working and being in the same position for a long time while working. Most employees stated that their current sitting position is uncomfortable, and can make employees experience fatigue at work. The purpose of this study was to analyze the relationship between sitting posture and the workload of PT Trans Marga Central Java employees. This study used a quantitative correlational approach. This study was conducted at the Trans Marga Central Java Office on Pedalangan Street, Banyumanik, Semarang City. The sampling technique used in this study was the total sampling technique, so the number of samples in this study was 73 employees. Data analysis was carried out using bivariate correlation analysis using Spearman correlation. A total of 54 respondents (74%) of Trans Marga Central Java Office employees had a fairly good sitting posture while the remaining 19 respondents (26%) had a good sitting posture. The level of workload of Trans Marga Central Java Office employees was highest in the category of workload that did not cause fatigue, namely 51 respondents (69.9%), while in the category of repairs needed but not urgent there were 22 respondents (30.1%). The significance value of the relationship between sitting posture and workload is 0.035 <0.05 and with a correlation coefficient of -0.247 indicating a significant negative relationship between sitting posture and workload of employees of the Central Java Trans Marga Office.